2010
DOI: 10.1016/j.flora.2010.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Stability of plant communities along a tropical inselberg ecotone in French Guiana (South America)

Abstract: International audienceWe questioned whether and how plant communities vary in space and time along an inselberg-rainforest ecotone in relation to present-day warming and whether biotic and non-biotic factors could explain the observed patterns. The study took place on a granitic inselberg in the French Guianan (South America) rainforest (Nouragues Natural Reserve: 4°5'N, 52°41'W). In a diachronic study (1995-2005) embracing a severe El-Niño event in 1997, we analysed vegetation structure and composition along … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 49 publications
0
9
0
1
Order By: Relevance
“…With greater soil depth, species adapted to higher moisture availability become dominant, with exclusion of dry-tolerant species. A great number of species (150 species) was also recorded on granite inselberg in the Nouragues Natural Reserve in French Guiana on a similar gradient (Sarthou et al 2010) and in ironstone (127 species) in the Serra dos Carajás, Amazonia-Brazil (Nunes et al in press). The diversity of habitats represents a variation in the resource availability and it correlates with a variation not only in the floristic composition, but also in the diversity of functional traits as a response to the different populations present on rock outcrop (de Paula et al 2015).…”
Section: Discussionmentioning
confidence: 94%
“…With greater soil depth, species adapted to higher moisture availability become dominant, with exclusion of dry-tolerant species. A great number of species (150 species) was also recorded on granite inselberg in the Nouragues Natural Reserve in French Guiana on a similar gradient (Sarthou et al 2010) and in ironstone (127 species) in the Serra dos Carajás, Amazonia-Brazil (Nunes et al in press). The diversity of habitats represents a variation in the resource availability and it correlates with a variation not only in the floristic composition, but also in the diversity of functional traits as a response to the different populations present on rock outcrop (de Paula et al 2015).…”
Section: Discussionmentioning
confidence: 94%
“…Many of these studies were conducted mainly in Africa and North America (e.g., in Africa: Burke, 2003a;Changwe and Balkwill, 2003;Porembski et al, 1996;in North America: Burbank and Platt, 1964;Wyatt and Fowler, 1977). Other studies were carried out within tropical South America in Brazil, Venezuela and French Guiana (e.g., Gröger and Barthlott, 1996;Porembski et al, 1998;Meirelles et al, 1999;Jacobi et al, 2007;Sarthou et al, 2010). Several of the studies focus on the application of island theory (MacArthur and Wilson, 1967;MacArthur, 1972) to outcrop biodiversity (Wyatt and Fowler, 1977), deal with succession and speciation processes (Burbank and Platt, 1964;Houle and Phillips, 1989;Williamson et al, 1997;Sarthou et al, 2009Sarthou et al, , 2010 or have shown very specific adaptations to these extreme environments (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Methods for chromosome analysis are according to Guerra & Souza (2002). Inselbergs, also known as rock outcrops, are granitic or gneiss geological formations from pre-Cambrian that stand out in a flat landscape (Sarthou & al., 2010). These formations are characterized by the presence of severe edaphoclimatic conditions in relation to the surrounding environment, which are important selective pressures for plant evolution and speciation.…”
Section: Subfamily Mapanioideae Tribe Chrysitricheaementioning
confidence: 99%